2018
DOI: 10.1080/1744666x.2018.1446829
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study comparing the pharmacokinetics of the potential biosimilar PF-06438179/GP1111 with Remicade® (infliximab) in healthy subjects (REFLECTIONS B537-01)

Abstract: CT.gov identifier NCT01844804.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Originally developed by Pfizer, PF-06438179/GP1111 (PF-SZ-IFX) is an infliximab biosimilar that is approved in the EU [12], Japan [13], the USA [14], and Brazil [15] for all eligible indications of reference infliximab (Remicade ® ) in each region. In preclinical studies, when compared with reference infliximab, PF-SZ-IFX was shown to have an identical primary amino acid sequence and similar biologic activity, including binding to TNF and inhibition of TNFinduced cell apoptosis in vitro [16]; in studies conducted in healthy subjects, PF-SZ-IFX also exhibited similarity to reference infliximab in its pharmacokinetic, safety, and immunogenicity profiles [17].…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed by Pfizer, PF-06438179/GP1111 (PF-SZ-IFX) is an infliximab biosimilar that is approved in the EU [12], Japan [13], the USA [14], and Brazil [15] for all eligible indications of reference infliximab (Remicade ® ) in each region. In preclinical studies, when compared with reference infliximab, PF-SZ-IFX was shown to have an identical primary amino acid sequence and similar biologic activity, including binding to TNF and inhibition of TNFinduced cell apoptosis in vitro [16]; in studies conducted in healthy subjects, PF-SZ-IFX also exhibited similarity to reference infliximab in its pharmacokinetic, safety, and immunogenicity profiles [17].…”
Section: Introductionmentioning
confidence: 99%
“…PF-06438179/GP1111 demonstrated similar toxicokinetic, tolerability, and antidrug antibody (ADA) responses to infliximab in a nonclinical in vivo toxicity study [ 15 ]. A phase I pharmacokinetics (PK) clinical study in healthy volunteers demonstrated similarity in PK, safety, and immunogenicity of PF-06438179/GP1111 to infliximab-US and infliximab-EU, as well as between infliximab-EU and infliximab-US reference products [ 16 ]. In the present double-blind, active-controlled, randomized, multinational study, we compared the efficacy, safety, PK, and immunogenicity of PF-06438179/GP1111 with infliximab-EU (Remicade®), each with background MTX therapy, as treatment for patients with moderate to severe active RA and inadequate response to MTX therapy.…”
Section: Introductionmentioning
confidence: 99%
“…and to outcomes of BE testing performed in the analysis. The study duration included an immunogenicity assessment with prespecified sample collections at 0 (predose), 336, 672, 1008 and 1680 hours post dose, and a PK evaluation with prespecified sample collections at 0 (predose), 8,12,24,48,72,96,120,144,168,192,264,336,504,672,840 and 1008 hours post dose, and an additional sample collection at 1680 hours post dose for facilitating the immunogenicity assessment at that time point. Both PK and immunogenicity samples were analysed at QPS, LLC (Newark, DE, USA) using validated bioanalytical procedures.…”
Section: What This Study Addsmentioning
confidence: 99%
“…While PK similarity determination with such a study design has been mostly shown to be highly efficient and informative in our experience, [5][6][7][8] there have been some complications associated with PK alterations caused by extensive immunogenicity response, especially when there was an imbalance in immunogenicity potential in terms of host-specific immunological characteristics between the test and reference groups. The impact of these complications on PK similarity determination remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%